MAPPING THE EVOLUTION AND CURRENT TRENDS ISLAMIC FINANCE: BIBLIOMETRIC ANALYSIS - Budi Nur Siswanto (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2023)
This bibliometric analysis aims to map research on Islamic finance. The data source is taken from the Scopus database, with the subject matter of Economics and business, from the search for the word